Le corps du saint dans l'hagiographie du Maghreb médiéval - Nelly Amri (Université de Provence, 2006)
This article attempts to think about the role given by medieval Maghreb hagiography to the body in the experience of sanctity and in the process of sanctification of a man or a woman. It focuses also on the body’s place in the recognition or consecration of this sanctity. Furthermore, this paper intends to detect the changes perceptible in sanctity criteria and the value that hagiography attaches to one or another sanctification path. It proposes also to look into the contemporaries’ perception of the saint’s body alive and the benefits they expect from it.